Going the Extra Mile: Managers and Supervisors as Moral Agents for Workers with Disability at Two Social Enterprises - Bartram, Timothy; Cavanagh, Jillian; Sim, Stephen; Pariona-Cabrera, Patricia; Meacham, Hannah (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2018)
This study examines the ethical management of workers with disability (WWD) employed at two social enterprises in Australia. Viewed largely through the spectrum of institutionally-based conflict in the employment relationship, this research draws on a framework of situated moral agency (Wilcox, 2012) to establish the ways in which WWD are afforded opportunities to engage in work and how managers and supervisors practise situated moral agency at the workplace. A qualitative case study approach is used with 62 participants through semi-structured interviews and focus groups.Key findings demonstrate supervisors constantly have to reshape and reinterpret human resource management (HRM) policies and practices to exercise and extend moral agency. This phenomenon suggests contradictions between moral agency and ethical management practice within current HRM regimes. The key message of the paper is that HRM does not always support the ethical management of WWD.Consequently, we question the ethical nature of contemporary HRM policy and practice for WWD, and argue for further research to unpack ethical ways to more effectively support WWD in the workplace. For WWD to be included at work, achieve life skills and their goals, managers and supervisors need to engage with their moral agency. Finally, we draw implications for management and employment relations theory and practice.